Numerical study on gas production from methane hydrate reservoir by depressurization in a reactor. (December 2020) - Shao, Yazhou; Yang, Longbin; Zhang, Qun; Wang, Shidong; Wang, Kunfang; Xu, Runzhang
Abstract: Gas hydrate is an abundant natural resource that has attracted much attention around the world. This paper aims at analyzing the gas production potential of methane hydrate reservoir by depressurization. The physical model of a cylindrical reactor is established and numerically simulated by using TOUGH + HYDRATE_v1.5. Based on the experimental parameters applied in our recent work, the cases are set to different wellhead pressures in a relatively broad range, covering that with ice formation and different thermal conductivities, especially involving ice formation. The simulation results indicate that for three cases with relatively higher wellhead pressures, the dissociation rate and the cumulative gas volume at the wellhead in the case of P W  = 2.0 MPa is much higher than in others due to its highest driving force. At the same wellhead pressure, increasing the thermal conductivity will slightly increase the gas production rate while not change the final gas production at the wellhead. Heat transfer shows an important role in hydrate dissociation, and the temperature gradient appears in the reservoir. Moreover, ice formation occurs under all three cases with different thermal conductivities, which indicates that increasing the thermal conductivity can not alleviate the rapid decrease of the reservoir temperature or ice formation caused by the higher driving force. There is an optimal pressure in which the gas production rate reaches the maximum by balancing the inhibition of ice formation and driving force. For the cases with ice formation, different production pressures do not yield significant differences in the hydrate dissociation characteristics. In actual exploitation, all the affecting factors should be considered to fulfill the most economical and efficient exploitation. Highlights: Lower production pressure leads to a higher gas production rate. Thermal conductivity hardly affects gas production rate with ice formation. Local temperature and pressure reflect dissociation characteristics. An optimal wellhead pressure exists by balancing the driving force and ice inhibition.